Internalization of The Value of Islamic Education Through The System of Kindness and Religious Harmony in Village Communities of 10 ULU Palembang - Samiha, Yulia Tri; Candra, Andi; Rusdi, Amir (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to analyze the internalization of the value of Islamic education through the kinship system and religious harmony in the people of Kampung 10 Ulu Palembang. This study uses a qualitative approach with naturalistic inquiry methods, while the data collection technique uses observation, interviews and document studies. Data analysis uses reduction techniques, data presentation, and conclusions. The results of this study conclude that (1) the internalization of the value of Islamic education to the community is carried out through an assimilation process that can unite the diversity that exists in the community of Kampung 10 Ulu Palembang; (2) the intensity of inter-ethnic renewal, namely people with Arab, Malay, and Chinese ethnicities without any discrimination; (3) a tolerant, assimilative and interactive kinship system creates inter-religious and inter-ethnic harmony or harmonization in the people of Kampung 10 Ulu Palembang. The implications of this research show that the process of assimilation in an area will create harmony and harmony between communities, especially through the internalization of the values of Islamic education.